Transformation Of Analysis Model To Business Process Model (International Journal of Engineering and Computer Science, 2018)
Software projects have become larger over the time and therefore the software requirements specifications have grown as well. One way to document requirements is the use of Use Cases, which describe the interaction of an actor with the desired system. Commonly used UML diagrams are - Use Case, Activity, Sequence, collaboration, statechart and Class diagrams. Use case and activity diagrams model the behavioral aspect of the system, whereas, Class diagrams represent the static design of a system. UML,being visual in nature, is easy to understand and communicate. However, as the number of Use Cases increases with the described functionality, the overview, the dependencies and possibly the execution order of Use Cases is lost more and more. Therefore, the task of locating specific Use Cases in large documents and avoiding contradictions becomes a hassle. Design and development of software has become much more complex in the last decade, resulting in evolution of design and development paradigms. Object oriented systems have thus become an integral part of more complex Service Oriented Architecture (SOA) to address complex issues. Automatic translation of UML use case and activity models to BPMN design elements would ensure consistent evolution of Object oriented systems to Service oriented paradigm.